Faktor-Faktor Yang Memengaruhi Adopsi Inovasi Teknologi - Muhammad Reza Bachri; Yusniar Lubis; Gustami Harahap (Jurnal Ilmiah Pertanian ( JIPERTA), 2019)
The purpose of this research is to know the factors that affect the adoption of technological innovation by farmers of rice paddies in the villages the district Percut Sei Tuan of the Deli Serdang. The results in the village of Kolam showed that the age of farmers to give effect to the adoption of technological innovation by farmers of rice paddies in the village Kolam where F-count of 2.694 and t-count of 2.301 and t-table 7.574 with the level of 5%. Education to give effect to the adoption of technological innovation by farmers ofÂ  rice paddies where F-count 2.694 and t-count of 1.148 and t-table7.574 with the level of 5%. The land gives effect to the adoption of technological innovation by farmers of rice paddies. Where F-count of 2.694 and t-count of 0.203 and t-table 7.574 with the level of 5%. Experience give effect to the adoption of technological innovation by farmers of rice paddies. Where F-count of 2.694 and t-count of 2.694 and t-table 7.574 with the level of 5%. Indonesian gives effect to the adoption of technological innovation by farmers of rice paddies. Where F-count of 17.889 and t-count of 4.230 and t-table 5.480 with the level of 5%.